In vitro and Ex vivo Antiparasitic Effect of Rheum ribes L. Extract Against the Hydatid Cyst Protoscoleces - Mahmoudvand, Hossein; Saki, Mojgan; Kiani, Ali A.; Taban, Tina; Shahmoradi, Mohammad Kazem (Infectious Disorders - Drug Targets, 2021)
Background: Cystic echinococcosis is a zoonotic infection in humans and herbivorous animals occurring worldwide, which is caused by the larva stage of Echinococcus granulosus. Rhubarb (Rheum ribes L.) as an herbal medicine has various therapeutic properties such as antioxidant, anticancer, and antimicrobial. With respect to the potential of the biological activities of this plant in traditional and modern medicine, we aim to examine its protoscolicidal effects against E. granulosus protoscoleces in vitro and ex vivo. Methods: Collected protoscoleces from liver hydatid cysts of infected sheep were exposed to the different concentrations of the extract (225, 450, 900 mg/mL) for 5-60 min in vitro and ex vivo. Then, by using the eosin exclusion assay, the viability of protoscoleces was studied. Results: R. ribes extract had a potent protoscolicidal activity in vitro ; at 450 and 900 mg/ml, it killed 56.3 and 100% of protoscoleces, respectively, after 10 min of exposure. In ex vivo assay, the extract needed more time to kill the protoscoleces than the in vitro; so that at the concentration of 900 mg/mL, all protoscoleces were killed after 15 minutes. Conclusion: The obtained results exhibited the potent protoscolicidal effects of R. ribes extract, particularly at the concentration of 900 mg/ml, which completely killed the parasite after <15 min of exposure. However, more supplementary studies are required to verify these findings by assessing animal models and clinical subjects.
Keywords: Echinococcus granulosus